Antimalarial Activity of Tinospora baenzigeri against Plasmodium berghei-Infected Mice. (5th September 2019) - Ounjaijean, Sakaewan; Kotepui, Manas; Somsak, Voravuth
Abstract : Plant species of the genus Tinospora (Menispermaceae) possess several pharmacological properties, and T. crispa has been reported to have antimalarial activity. T. baenzigeri (Chingcha Chalee) is a rich source of terpenes and quinoline alkaloids; however, it still has not yet been investigated the antimalarial activity of this plant extract. Hence, this study was aimed to evaluate the antimalarial activity of T. baenzigeri stem extract against Plasmodium berghei- infected mice. The aqueous crude extract of T. baenzigeri stem was prepared using a microwave-assisted method and tested for acute toxicity in mice. For evaluating the antimalarial activity in vivo, the standard 4-day test was carried out using groups of ICR mice infected with P. berghei ANKA administered orally by gavage with the extract (100, 250, and 500 mg/kg) for 4 consecutive days. Parasitemia, body weight, packed cell volume, and mean survival time were then measured. It was found that the aqueous crude extract of T. baenzigeri stem did not exhibit any sign of toxicity up to the dose of 2, 000 mg/kg. The extract significantly (P < 0.01 ) inhibited parasitemia in a dose-dependent manner, with 22.02%, 50.81%, and 74.95% inhibition. Moreover, the marked prevention of body weight loss and packed cell volume reduction was observed at doses of 100, 250, and 500 mg/kg of extract-treated mice. Additionally, the extract prolonged the mean survival time of P. berghei- infected mice, compared to the untreated group. In conclusion, the aqueous crude extract of T. baenzigeri stem has demonstrated potent antimalarial activity against P. berghei- infected mice with prolonged mean survival time and prevention of body weight loss and packed cell volume reduction.